Anatomia foliar e floral de Amorimia (Malpighiaceae) e suas aplicações filogenéticas - Ana Caroline Marques Pereira Mello (2017)
Malpighiaceae belongs to Malpighiales andcomprisesabout 1,300 species and 77 genera. Most species (88.5%) are confined to the Neotropics and few species (11.5%) occur in the Paleotropics. The majority of its species occur in South America, being one of the ten most important families of flowering plants in the Brazilian Cerrado. The monophyly of this family is largely supported, but intergeneric relationships are still unclear. The genus Amorimia W.R.Anderson presents few studies regarding its taxonomy and infrageneric delimitations remain unsolved. Considering the importance of this family and the number of recent segregated genera, as well as the lack of studies focusing on these subjects, our goal was to analyze and characterize leaf and floral anatomy, especially vasculature, from all Amorimia species, aiming to highlight characters to help on species delimitation and on phylogenetic relationships within this genus. In Chapter I, leaf characters were indicated as new synapomorphies for the genus Amorimia and other groups, recognized in an extensive and detailed list of 89 characters that can be used for other studies including Malpighiaceae and other botanical families. In addition, the Chapter II presents the vasculature of floral buds, which revealed important data, for instance the conformation of carpels ventral bundles and the interpretation of different fusion of vascular traces, as well as vasculature of sepals and glands, which provide relevant data for understanding the evolutionary process in the family and the delimitation of species. Therefore, the results of this work represent subsidies for studies on anatomy, mainly for Malpighiaceae, because there are few works published on anatomy of this family and, for Amorimia, this approach is completely unpublished.